Control of seismically excited benchmark highway bridge with variable frequency pendulum isolator. (1st January 2012) - Madhekar, Suhasini N.; Jangid, R.S.
Earthquake response of benchmark highway bridge, isolated with variable frequency pendulum isolator (VFPI) is investigated under six earthquakes, using a simplified lumped mass finite element model. The isolators are installed between deck-ends and abutments. Seismic response of the bridge with VFPI is compared with that of the bridge with the friction pendulum system (FPS). Parametric studies are carried to find the optimum values of coefficient of friction and isolation period of the FPS; and frequency variation factor, initial time period and coefficient of friction of VFPI. The response of the bridge with VFPI is compared with the uncontrolled case, with FPS, and that controlled by alternate sample control strategies. Significant reductions in base shear, base moment, deck displacements and bearing displacements are observed using FPS and VFPI. It is concluded that these isolators are quite effective in substantially reducing peak response quantities of the bridge, comparable to that of the sample controllers.